The Impact of an Educational Program on Developing Emotional Intelligence Among Primary School Students - Fadhil Shakir Hassan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aimed to measure the impact of an educational program on developing emotional intelligence skills among fifth-grade primary school students in several mixed-gender schools in Baghdad. The research adopted the experimental scientific method, utilizing a pre-test and post-test design for two groups. The sample was randomly selected from a research population of 150 students, with 100 students chosen as the study sample. These students were divided into two equal groups: a control group (50 students) and an experimental group (50 students). The educational program was designed based on free dialogue, storytelling, as well as games and activities that help children understand and develop emotional intelligence skills in a smooth and constructive manner. The program was implemented over a period of 12 weeks, from March 1, 2024, to June 1, 2024, exclusively for the experimental group. Daniel Goleman’s 2002 emotional intelligence model was used as a measurement tool, as it is suitable for the age group of the study sample. The results indicated statistically significant differences between the mean scores of the experimental and control groups in the pre-test and post-test, demonstrating the clear impact of the program on the experimental group. Additionally, the results showed no statistically significant differences between male and female students within the experimental group. The researcher recommends adopting the program in primary schools and suggests organizing training courses for primary school teachers on intelligence development in children. Furthermore, the researcher proposes integrating intelligence development into teacher guides and increasing activities that focus on enhancing cognitive abilities.